Las leyes de 1884 en Costa Rica - Miranda Fonseca, Héctor (2014)
The present paper attempts to demons trate a philosophical analysis of the period comprehended between 1880 and 1890, when the liberal laws of 1884 were inacted. It ajso attempts to demonstrate that such laws instead have a positivist liberal ideology.